The Role of Anti-Smoking Campaign In Attempting To Quit Smoking - Duygu Aydın; Kamile Marakoğlu (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
In the study, the role of the “Smoke-free Air Space” campaign advertisements, hotlines, the ban on smoking in enclosed spaces, polyclinics for quitting smoking, etc. conducted by the Ministry of Health in quitting smoking was questions. In the idea of terminating cigarette smoking, which has significant adverse effects on individual and social health, knowing which factors are effective to what extent will contribute to solving this problem. The purpose of this study is to reveal the factors effective in the attempt to quit smoking and to question the effectiveness of the Smoke-free Air Space Campaign, conducted by the Ministry of Health, on these attempts made by the patients to quit smoking. The method used in the study is cross-sectional research; in the study in which the data were collected through survey method, the exposure of the patients 206 patients that visited the centers of having cigarette smoking quit, which operate within Family Medicine of Medical Faculty Hospital at the Selcuk University, to the campaign against smoking, their level of recollection, their attitudes, and the role of campaign factors in their attempts to quit smoking were questioned. The rate of the participants that recalled the Smoke-free Air Space Campaign was high. They were exposed to the campaign ads most through television. The participants expressed their negative feelings about smoking when asked what they thought about smoking. They said that smoking is dangerous for health and stated that some external factors such as family, friends etc. are effective in smoking. Two factors were found to have been effective in the attempts to quit smoking; these are “the campaign factor” and “the environment-health factor”. The campaign factor, which was found to have been the more effective one, covers such factors as ads, TV programs, the prohibition of smoking in enclosed spaces, the efforts in cigarette-quitting clinics as a whole